INTERNALIZATION OF RELIGION IN THE DALAIL KHAIRAT FASTING TRADITION AT JEKULO ISLAMIC BOARDING SCHOOL, KUDUS - indal abror; Muhammad Rizky Romdonny (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Dalail Khairat fasting is a type of fasting that is practiced at the Darul Falah Jekulo Islamic Boarding School, Kudus. This fast is carried out for 3 consecutive years. In its implementation, the participants went through several stages of fasting. This paper attempts to discuss how the practice of fasting is carried out, the chain of fasting practice, namely the transmission of knowledge and the foundation of authoritative texts, as well as the subject's reception in the implementation of fasting. This research is a field research. Technical data analysis was carried out qualitatively-descriptively. Using an analysis of historical methods, the author concludes that the genealogical roots of Dalail Khairat's fasting go back to the first mujiz, namelySayyid al-Imam Muhammad bin Sulaiman al-Jazuli. In addition, the Dalail's fasting riyadah has an influence on the mental and psychological state of the practitioner. This shows that the Darul Falah Islamic Boarding School is able to maintain this fasting tradition in a sustainable manner.